-7(1-2x)+8=-83

Simple and best practice solution for -7(1-2x)+8=-83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(1-2x)+8=-83 equation:


-7(1-2x)+8=-83

We simplify the equation to the form, which is simple to understand
-7(1-2x)+8=-83

Reorder the terms in parentheses
+(-7+14x)+8=-83

Remove unnecessary parentheses
-7+14x+8=-83

We move all terms containing x to the left and all other terms to the right.
+14x=-83+7-8

We simplify left and right side of the equation.
+14x=-84

We divide both sides of the equation by 14 to get x.
x=-6

See similar equations:

| g(x)=3(5)x | | 4r^2-r+3=0 | | 3v+6=9-3(2v-2) | | x+3(x+6)=4(2x+1) | | 4(3z-3)=18 | | (2x-17)/5=-5 | | -11=3(v-7)-8v | | 13+x+2x=6x+1 | | 4x^2+8x+36=0 | | 73/100=81 | | 4x+4+8+2x=3(x+5) | | 3u^2+17u+24=0 | | 4x+6(x+2)=35 | | (5x-3)/9=-2 | | 2/3x5/6x14x18 | | -8(3x+1)-4=11 | | 3000(x+100)=2000(x-100) | | -4-8y=35 | | 2(x-5)(x+4)=0 | | 2x-5+8x=7-4x-12 | | 2(14+2x)=8(2+x) | | 2•1/3•3.14•25•25•25 | | 2u^2+15u+28=0 | | 4x+9x-34=68-4x | | -14=-3x | | 3x+7=5x+1-x | | 10/12*1/4= | | y=log^4(3x+11)-5 | | 6.1-0.25(x-8)=0.7x+0.3(x-3) | | 8y+9=6y+14 | | 4(.5-.25y)+y=2 | | 5e^2x=13 |

Equations solver categories